2020
DOI: 10.3389/fmicb.2020.00904
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Lactobacillus Species of Stilton Cheese Relates to Site of Isolation

Abstract: This study has characterized the dominant non-starter Lactobacillus species isolated from different sites in a Stilton cheese to establish its diversity, stress-tolerance, antimicrobial activity and potential contribution to quality of cheese. Fifty-nine Lactobacillus isolates were cultured from the outer crust, blue veins and white core of the cheese and were speciated phenotypically and by 16S rDNA sequence analysis. Lactobacillus plantarum was the dominant species detected with only two isolates identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The microbial ecology of cheese involves a rich and complex interaction between the starter lactic acid bacteria (SLAB) and the non-starter lactic acid bacteria (NSLAB). The SLAB in the cheese decline throughout ripening while growth of NSLAB increases as ripening progresses (Gantzias et al, 2020;Mugampoza et al, 2020;Settanni and Moschetti, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The microbial ecology of cheese involves a rich and complex interaction between the starter lactic acid bacteria (SLAB) and the non-starter lactic acid bacteria (NSLAB). The SLAB in the cheese decline throughout ripening while growth of NSLAB increases as ripening progresses (Gantzias et al, 2020;Mugampoza et al, 2020;Settanni and Moschetti, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the L. brevis strains are known for their probiotic potential, and a few of them are employed as starter cultures ( Annuk et al, 2003 ). L. brevis is a common LAB species found in the microbiota of fermented cheeses ( Guley et al, 2014/15 ; Mugampoza et al, 2020 ; Skelin et al, 2012 ). The isolation of the L. brevis KT38-3 strain from artisanal Kargi Tulum cheese is in accordance with the data in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the L. brevis strains are known for their probiotic potential, and a few of them are employed as starter cultures (Annuk et al, 2003). L. brevis is a common LAB species found in the microbiota of fermented cheeses (Skelin et al, 2012;Guley et al, 2014;Mugampoza et al, 2020).…”
Section: Genotypic Identification Of Kt38-3 Strainmentioning
confidence: 99%
“…Cocci, or rod-shaped, gram-positive, acid-tolerant, and non-sporing LAB is the key microorganism in GABA production (Yogeswara et al 2020b ). Furthermore, various Lactobacillus species, including, L. brevis (Mancini et al 2019 ; Seo et al 2013a ), L. buchneri (Mugampoza et al 2020 ), L. delbrueckii subs. Bulgaricus (Câmara et al 2019 ; Gangaraju et al 2014 ), L. plantarum (Zhuang et al 2018 ), and L. helveticus (Li et al 2020 ) have demonstrated significant potential in GABA biosynthesis and strong endogenous GAD activity.…”
Section: Gaba-producing Strains and Metabolic Pathwaymentioning
confidence: 99%